Effect of interface moisture content on the interlayer bond strength - Gowrikanthan Nishangani; Lees Janet M. (MATEC Web of Conferences)
Reducing carbon dioxide emissions in concrete construction is a global priority. One potential solution is functionally graded concrete, where concretes with different properties are used within a single structural element to reduce environmental impact. For functionally graded members with horizontal concrete layers, the mechanical performance of the interface zones is critical for structural behaviour. Factors such as the casting technique, concrete grade, substrate surface texture, time delay between layer deposition and moisture content all influence the interlayer properties. While studies have explored these factors, the impact of interface moisture on bond strength remains inconclusive. This research evaluates the relationship between the interface surface moisture and interlayer bond strength. Splitting tensile tests were conducted on 40 fresh-on-fresh cast layered specimens with low-slump or high-slump concrete mixes. The substrate surface moisture was controlled by drying or adding a known volume of water. In the low-slump mixes a high surface moisture content led to a 10 % reduction in bond strength, likely due to the formation of a weaker transition layer. In high-slump mixes, moisture removal resulted in 11 % reduction, potentially due to surface drying and smoothing. These findings highlight the importance of optimising interface moisture conditions to ensure adequate interlayer bonding in functionally graded concrete.